When east meets west American and Chinese influences on early Indonesian action cinema: the list of filmography of early Indonesian action movies (1926-1941) (Plaridel, 2014)
Access online through this link: https://www.plarideljournal.org/article/when-east-meets-west-american-and-chinese-influences-on-early-indonesian-action-cinema-the-list-of-filmography-of-early-indonesian-action-movies-1926-1941